Circulating miR-34a and Bone Mineral Density of Brazilian Very-Old Adults - Otávio T. Nóbrega; Gilberto S. Morais-Junior; Nayara I. Viana; Sabrina T. Reis; Diego I. V. Perez; Wladimir M. Freitas; Andrei C. Sposito; Kátia R. M. Leite; Miguel Srougi (Journal of Aging Research)
The human aging is marked by several body changes, including in bone mineral density (BMD). Research shows that microRNAs are important modulators of bone metabolism. The present research aims to analyze the whole blood concentration of 10 selected microRNAs (miRs) and their association with absolute and relative scores of BMD in specific osseous site of Brazilian very-old adults. Forty noninstitutionalized and apparently healthy, very old (≥80 years) outpatients were eligible for research. Anthropometry, biochemistry, and densitometry measurements were performed along with coronary artery calcification (CAC) scores and tested across total circulating levels of microRNAs. As expected, the relative BMD scores for the lumbosacral region (L1 to S5) and for the femoral head and neck observed in the sample denote weakened bone architecture, compatible with prevalent osteopenia and osteoporosis. In this context, one single significant association was found, and negatively implicated the miR-34a-5p with both absolute (β = −0.36, P=0.001 for BMD) and relative (β = −0.43, P=0.001 for T-score) densitometry indexes of the femoral head (adjusted to sex and physical activity practice), but not with the other sites. No difference in total blood concentrations of the miRs was found according to CAC scores. Our findings indicate greater circulating levels for miR-34a-5p among very-old adults who display the lowest scores of BMD, being a finding consistent with a modest contribution of the miR (along with co-variables) to the mineralization of that site. Attesting clinical relevance of our findings demands forthcoming studies.